The economic impact of hypercholesterolemia and mixed dyslipidemia: A systematic review of cost of illness studies. - Pietro Ferrara (Public Library of Science (PLoS), 2021)
Hypercholesterolemia is a clinically relevant condition with an ascertained role in atherogenesis. In particular, its presence directly correlates to the risk of atherosclerotic cardiovascular disease (ASCVD). As known, cardiovascular diseases pose a significant economic burden worldwide; however, a clear picture of the economic impact of ASCVD secondary to hypercholesterolemia is lacking. This study aiming at conducting a systematic review of the current literature to assess the economic impact of familial hypercholesterolemia (FH), non-familial hypercholesterolemia (non-FH) or mixed dyslipidemia. A literature search was performed in Medline/PubMed and Embase database up to September 1st, 2020, exploring evidence published from 2010. The literature review was conducted in accordance with PRISMA guidelines. To be included the studies must be conducted on people who have been diagnosed with familial hypercholesterolemia, non-familial hypercholesterolemia or mixed dyslipidemia, and report data/information on costs attributable to these conditions and their sequelae. A total of 1260 studies were retrieved. After reading the titles and abstract, 103 studies were selected for full reading and eight met the criteria for inclusion. All but one studies were published in the American continent, with the majority conducted in US. An observational design with a prevalence approach were used and all estimated the economic burden of CVD. Direct cost estimates as annual average health expenditure on all population, ranging from $17 to $259 million. Few studies assessing the economic impact of hypercholesterolemia are available in the literature and new researches are needed to provide a more updated and reliable picture. Despite this scarceness of evidence, this review adds important data for future discussion on the knowledge of the economic impact of hypercholesterolemia and costs of care associated to this condition, with important implication for public health researches and novel therapies implementation.